PERINATAL CARDIOLOGY: PREGNANCY AND CONGENITAL HEART DEFECTS - Shopulotova , Z.A.; Zubaydilloeva , Z.Kh. (Eurasian Journal of Academic Research, 2023)
The incidence of congenital heart defects varies widely and ranges from 2.4 to 14.15%. Every year, more than 30,000 children are born worldwide with congenital heart defects. Many of these patients are young women planning to carry a pregnancy to term and give birth to a healthy child. In women with congenital heart defects during pregnancy, the risk of developing heart failure, arrhythmia, cerebrovascular diseases, and embolism, leading to death, increases. The course of pregnancy is complicated by fetal growth restriction, premature birth, preeclampsia, newborns have a lower birth weight, and the risk increases.